2011
DOI: 10.1108/09615531111095094
|View full text |Cite
|
Sign up to set email alerts
|

Design optimisation of a regenerative pump using numerical and experimental techniques

Abstract: Regenerative pumps are the subject of increased interest in industry as these pumps are low cost, low specific speed, compact and able to deliver high heads with stable performance characteristics. The complex flow-field within the pump represents a considerable challenge to detailed mathematical modelling. This paper outlines the use of a commercial CFD code to simulate the flow-field within the regenerative pump and compare the CFD results with new experimental data. A novel rapid manufacturing process is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…They confirmed that the side‐blade angle has a significant effect on the performance of the side channel pump. The FLUENT software was applied in the examination of the flow of the fluid in this kind of pump by Quail et al and Quail . The experimental results corroborated the CFD analysis.…”
Section: Effects Of the Geometrical Design Of The Parameters Of The Smentioning
confidence: 66%
“…They confirmed that the side‐blade angle has a significant effect on the performance of the side channel pump. The FLUENT software was applied in the examination of the flow of the fluid in this kind of pump by Quail et al and Quail . The experimental results corroborated the CFD analysis.…”
Section: Effects Of the Geometrical Design Of The Parameters Of The Smentioning
confidence: 66%
“…Their inherent ability to provide multi-staging using only one impeller provides much higher heads compared to machines of similar tip speeds [13,15]. The head rise can be increased even further by incorporating several pumping stages on a common shaft [11].…”
Section: Applicationsmentioning
confidence: 99%
“…Perhaps what really distinguishes the RLR pump is its ability to develop high heads at relatively low flow rates in only one impeller stage [7][8]. It shares similar operating characteristics to another pump classification, positive displacement: the power is directly proportional to head, with a maximum power required at shutoff and a very steep, nearly straight head-capacity curve [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quil et al used a commercial code to investigate the fluid flow in a regenerative pump. They also carried out a new method of manufacturing to evaluate the influence of change in blade geometry on the efficiency of regenerative pump [11,12]. An experimental study was accomplished by Choi et al to investigate the effect of the impeller blade angle and its shape on regenerative pump performance.…”
Section: Introductionmentioning
confidence: 99%